Distinct MJOs Under the Two Types of La Niña. Issue 23 (1st December 2022) - Wei, Yuntao; Ren, Hong‐Li
Abstract: El Niño‐Southern Oscillation (ENSO) strongly influences the interannual variations of Madden‐Julian Oscillation (MJO)—the dominant mode of tropical intraseasonal variability. Previous studies have revealed more about the impacts of the diversified El Niño on MJO, but less about those of the La Niña diversity. Using observations and global climate model experiments, this study demonstrates that MJO undergoes distinct variations and Pacific teleconnections when La Niña varies between eastern‐Pacific (EP) and central‐Pacific (CP) types. Compared to the CP La Niña, MJO under the EP La Niña is more energetic over the southern Maritime Continent–South Pacific Convergence Zone and can propagate faster and further with a broader zonal circulation scale over the Indo‐Pacific warm pool. The stronger and faster MJO under the EP La Niña is associated with more vigorous ascending motions, higher moisture content and stronger moistening in the lower‐level atmosphere ahead of the MJO deep convection. Although the meridional moisture advection exists as the fundamental mechanism of MJO eastward propagation, the distinct MJO under the two types of La Niña primarily results from the different lower‐tropospheric moistening due to the zonal moisture advection. Both the background mean and anomalous zonal winds and moisture gradients are stronger under the EP La Niña, thereby causing a remarkable invigoration effect of zonally advective moistening. Diverse extratropical circulation responses of distinct MJOs are also discussed. These results should improve our understanding of the whole ENSO diversity paradigm that influences MJO and teleconnections. Plain Language Summary: The Madden‐Julian Oscillation (MJO) intensity and propagation undergo significant year‐to‐year variations, behind which the leading mode of the tropical 2‐ to 7‐year variability (e.g., El Niño‐Southern Oscillation, ENSO) plays an important role. Despite many studies focused on the impacts of the diversified ENSO warm phases on MJO, no one has ever tried to understand the possible MJO variations in different types of ENSO cold phases (i.e., La Niña). Here, we find that MJO tends to be broader, stronger and faster when a La Niña has its cooling center over the eastern Pacific. However, when the La Niña cooling peaks over the central Pacific, the atmosphere ahead of MJO becomes drier and more stabilized, and thus the MJO eastward propagation is constrained, slower and weaker. The remote influences of MJO over North America (East Asia) are likely stronger when the La Niña cooling center shifts eastward (westward). These results help us construct a whole paradigm of ENSO diversity influencing MJO and also support the necessity to consider the two types of La Niña when exploring different ENSO impacts on global weather and climate. Key Points: The Madden‐Julian Oscillation (MJO) under the eastern‐Pacific La Niña is broader, stronger and faster than under the central‐Pacific La Niña The distinct MJOs under the two types of La Niña are largely shaped by the different zonal moisture advection The distinct MJOs may cause different extratropical influences under the two types of La Niña